Anterior Spinal Artery Syndrome-A Rare Cause Of Acute Onset Quadriparesis (Nepal Journal of Neuroscience, 2025)
Spinal cord infarction secondary to Anterior Spinal Artery Syndrome is a very rare condition. It usually occurs secondary to aortic surgery, thromboembolism, aortic dissections and hypoperfusion. We present here a rare case of a 64 year old patient who presented with acute onset of quadriparesis and was found to have Anterior Spinal Artery syndrome. Initial imaging was normal while repeat imaging after forty eight hours showed features of cervical cord infarction. He was managed conservatively with intravenous corticosteroids, low molecular weight heparin and anti platelet agents and had improvement in motor power after treatment.